Monitoring the Neuroinflammatory Response Following Acute Brain Injury - Thelin, Eric Peter; Tajsic, Tamara; Zeiler, Frederick Adam; Menon, David K.; Hutchinson, Peter J. A.; Carpenter, Keri L. H.; Morganti-Kossmann, Maria Cristina; Helmy, Adel (Frontiers in Neurology, 2017)
Traumatic brain injury (TBI) and subarachnoid haemorrhage (SAH) are major contributors to morbidity and mortality. Following the initial insult, patients may deteriorate due to secondary brain damage. The underlying molecular and cellular cascades incorporate components of the innate immune system. There are different approaches to assess and monitor cerebral inflammation in the neurological intensive care unit. The aim of this narrative review is to describe techniques to monitor inflammatory activity in patients with TBI and SAH in the acute setting. The analysis of pro- and anti-inflammatory cytokines in compartments of the central nervous system (CNS), including the cerebrospinal fluid (CSF) and the extracellular fluid (ECF), represent the most common approaches to monitor surrogate markers of cerebral inflammatory activity. Each of these compartments has a distinct biology that reflects local processes and the cross-talk between systemic and CNS inflammation. Cytokines have been correlated to outcomes as well as ongoing, secondary injury progression. Alongside the dynamic, focal assay of humoral mediators, imaging, through positron emission imaging (PET), can provide a global in vivo measurement of inflammatory cell activity, which reveals a long-lasting process following the initial injury. Compared to the innate immune system activated acutely after brain injury, the adaptive immune system is likely to play a greater role in the chronic phase as evidenced by T-cell mediated auto-reactivity towards brain specific proteins. The most difficult aspect of assessing neuroinflammation is to determine whether the processes monitored are harmful or beneficial to the brain as accumulating data indicates a dual role for these inflammatory cascades following injury. In summary, the inflammatory component of the complex injury cascade following brain injury may be monitored using different modalities. Using a multi-modal monitoring approach can potentially aid in the development of therapeutics targeting different aspects of the inflammatory cascade and improve the outcome following TBI and SAH.